Factors predicting organizational commitment among nurses in state hospital Malaysia - Lee, Siew Pien; Chitpakdee, Bunpitcha; Chontawan, Ratanawadee (2011)
With the rate of national nursing shortage increasing, organizational commitment is an extremely important factor for promoting retention of nurses. This descriptive predictive study aimed to determine the level of organizational commitment and determine the ability of perceived organizational support; the sub components of job satisfaction including pay, autonomy, task requirement, organizational policies, interaction, and professional status and years of experience among nurses in predicting organizational commitment. Sample included 416 nurses working in four state hospitals in Malaysia. The demographic data form developed by the researcher, Survey of Perceived Organizational Support developed by Eisenberger et al (1986), Index of Work Satisfaction developed by Stamps (1997) and Organizational Commitment Questionnaire developed by Mowday, Steers and Porter (1979) were used to collect data. Cronbach’s coefficient alpha of the questionnaires were .80, .80 and .95, respectively. The Cronbach’s coefficient alpha of the sub components of Index Work Satisfaction ranged from .67 to .72. Descriptive statistics and stepwise multiple regression were used to analyze data. The results revealed that (1) almost half of the samples (48.80 %) had high organizational commitment, 44.23 % of the samples had moderate organizational commitment, and another 6.97 % of the samples had low organizational commitment. (2) Professional status, autonomy, interaction, task requirement and years of experience could predict the organizational commitment (b = .52, .17, p < .01; b = .13, .11, .09, p < .05 respectively). Overall, all predictors explained 33% of variability in the organizational commitment among nurses in state hospitals. Results of this study provide information for nurse administrators to maintain these predicting factors in nursing practice in order to foster a high level of organizational commitment among the nurses.